Time-Varying Inflation Co-Movement: Dynamic Factor Model with Global, Group, and Country-Specific Factors - Tunç, Ahmet; Nazlıoğlu, Şaban; Yücel, Ali Gökhan (Elsevier, 2026)
This study examines global inflation co-movement by employing a dynamic factor model with time-varying parameters and stochastic volatility to extract global, group, and country-specific factors across 86 developed and developing economies from 1971 to 2023. The results reveal that (i) the global factor has gradually receded as the primary source of inflation variation, giving way to more group- or country-specific dynamics—though brief episodes of global synchronization reemerge during major crises; (ii) the group factor dominates inflation variation in developed countries; and (iii) the country-specific factor remains the main driver of inflation in developing countries.
Keywords: Inflation; Co-Movement; Dynamic Factor Model; Time-Varying Parameter; Stochastic Volatility